2021
DOI: 10.1177/01939459211028666
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Duration and Hand Grip Strength among COPD Patients

Abstract: This study aimed to evaluate the association between night-time sleep duration and hand grip strength (HGS) among patients with chronic obstructive pulmonary disease (COPD). Participants aged ≥45 years were included in a nationally representative investigation clinical study in 2015. HGS was measured using dynamometers. The data on night-time sleep duration, sociodemographic information, and health-related variables were systematically collected. For analysis, sleep duration was categorized as <5 h, 5–7 h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, people with COPD who were unmarried tended to have shorter sleep duration than those who were married. This evidence supports previous findings that people with less than a high school education most commonly reported short sleep ( 17 ) and that being married was associated with 9 hours of nighttime sleep duration in the COPD population ( 16 ). We also found that depression was significantly associated with short sleep duration in people with COPD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, people with COPD who were unmarried tended to have shorter sleep duration than those who were married. This evidence supports previous findings that people with less than a high school education most commonly reported short sleep ( 17 ) and that being married was associated with 9 hours of nighttime sleep duration in the COPD population ( 16 ). We also found that depression was significantly associated with short sleep duration in people with COPD.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has reported that people with COPD had shorter sleep duration than people without COPD, showing 4.7 hours of sleep on average ( 15 ). Additionally, one study reported that 63.6% of people with COPD had sleep duration of less than 7 hours ( 16 ); another found that people with COPD and insomnia had 6.3 hours of mean sleep duration ( 10 ). Thus, our results are generally consistent with previous findings that short sleep duration is prevalent in people with COPD.…”
Section: Discussionmentioning
confidence: 99%